2017
DOI: 10.1111/jpc.13484
|View full text |Cite
|
Sign up to set email alerts
|

Survey of neurodevelopmental allied health teams in Australian and New Zealand neonatal nurseries: Staff profile and standardised neurobehavioural/neurological assessment

Abstract: Although neurodevelopmental allied health teams and standardised neurobehavioural/neurological assessments are valued by many, there was little consistency across Australian and New Zealand neonatal nurseries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The questionnaire items were developed and modified with reference to previous studies in Canada, Australia, and Korea. 7,[10][11][12] The finalized questionnaire consisted of 3 sections. The cover explained the purpose, structure, filling out, and retrieval of the questionnaire.…”
Section: Development Of Questionnaire Itemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire items were developed and modified with reference to previous studies in Canada, Australia, and Korea. 7,[10][11][12] The finalized questionnaire consisted of 3 sections. The cover explained the purpose, structure, filling out, and retrieval of the questionnaire.…”
Section: Development Of Questionnaire Itemsmentioning
confidence: 99%
“…An Australian study also reported that the percentage of highly educated physical therapists with a master's degree or higher is particularly high among professions involved in the NICU. 10 As the field of neonatal intensive care also requires ad- In regard to the allocation of neonatal PT related work in Korea, there was a difference in the duration of neonatal PT (per session)…”
Section: General Characteristics Of the Study Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…These significant long-term ramifications highlight the importance of early intervention to ameliorate long term impacts and include neuroprotective developmental care strategies and therapeutic interventions in NNU (Altimier & Phillips, 2013;AOTA, 2018;Nightlinger, 2011;RCOT, 2017). Evidence based practices such as individualised developmental care, and allied health team interventions, including Occupational Therapy, have become an integral part of NNU practice (Allinson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reflect that the literature is currently limited, given factors mentioned above. Correspondingly, language intervention (as a component of neurodevelopmental care) and speech‐language pathology services are not standard in neonatal hospital contexts . Yet, if the growing number of publications is any indication, interest is increasing, and a more robust evidence base will soon emerge.…”
mentioning
confidence: 99%